The development of entrepreneurial capacity and business activity of students of educational establishments using information and communication technologies - L. A. Danchenok; N. V. Komleva; Zh. B. Musatova (Открытое образование (Москва), 2016)
The article is devoted to problems of organizational and methodical process modeling of the entrepreneurial potential and business activity of students of educational institutions through the use of Smart-technologies. It is noted that the successful implementation of enterprise and business projects are the basis of economic development of society, with the main factor for the development of entrepreneurship in the country in the long term is to develop the entrepreneurial mindset of young people. Entrepreneurial younger generation reserve created for the period of study, will provide the subsequent decades of business operation, incomenot only to the owner, but also the composition of personnel of the company and, in general, the country. The specifics of perception of the new generation of knowledge, learning and the formation of professional skills is that their effectiveness depends, sometimes completely determined by the degree of use of information and communication technologies, not only in the preparation and implementation of knowledge by the learners, but also in the work themselves teachers. Therefore, an effective and modern instrument for achieving the development goals of the business potential and business students to provide such forms of work with students, which would stimulate their interest in entrepreneurship through the active use of information technologies. The organizational and methodological training model and a set of measures aimed at developing the entrepreneurial potential and business activity of the young generation. To a large extent the elements of our model successfully implemented in REU them. GV Plekhanov at the Faculty of “Marketing Business School and Entrepreneurship”, to carry out training business technologies in relevant areas of knowledge for the information society and the modern state of the economy – business intelligence, innovation and creative business, crisis and risk management, technological Strategic Management (MBA program and a mini-MBA, retraining and refresher courses, professional orientation of varying lengths; trainings and workshops). The main purpose – to form students practical skills and competence for business management in modern conditions. The goal of the entrepreneurial potential and business activity of youth should help to improve the system of vocational guidance work with students, the creation of a continuous training system, the integration of general and further education for the development of entrepreneurship and business activity in the educational institutions of higher and secondary levels of education. A number of recommendations on the organization of professional space ICT teacher and the use of various forms of work with students in order to effectively transfer knowledge, determine their entrepreneurial potential, and the development of entrepreneurial activity. Modern professional space ICT teacher, especially in applications such areas as business training, should be focused on mutual transfer of technologies in an integrated chain: education - science - practice.